Techniques To Exploit Vulnerabilities: Persuasion And Education In Chinese Police Interrogations. (4th September 2021) - Mou, Yu
Abstract: Drawing upon in-depth interviews with frontline police officers, this article examines persuasion and education as a psychological interrogation method routinely applied in Chinese police questioning. It analyses the three tactics employed by the interrogators in inducing the suspect to confess, including utilization of suspects' personal relationships, their hope for the uncertain future and memories of past experiences. These mechanisms correspond to the three forms of universal vulnerability shared by human beings, namely the individuals' susceptibility to human dependency, the predicament of irreversibility and uncertainty about the future. This article analyses the ways in which vulnerability as a universal human condition can be exploited by state coercion, and how this coercion produces the moral vulnerability of police.